THU0035 OX40L EXPRESSING NEUTROPHILS INDUCE CD4 T FOLLICULAR AND PERIPHERAL HELPER CELL DIFFERENTIATION IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Pappalardo, A.; Wojciechowski, E.; Odriozola, I.; Douchet, I.; Merillon, N.; Boizard-Moracchini, A.; Duffau, P.; Lazaro, E.; Doucey, M. A.; Mbow, L.; Richez, C.; Blanco, P.
Abstract : Background: Neutrophils have been described as potent antigen-presenting cells able to activate T cells by MHC/TCR interaction and costimulatory molecules in tumor immunity. However, little is known about the direct interaction between neutrophils and CD4 T cells with respect to systemic lupus erythematosus (SLE). We have previously shown that OX40L expressed by monocytes from SLE patients promote the differentiation of naïve and memory cells into IL21 secreting T cells that are able to help B cells 1, 2 . Objectives: In this study, we investigate OX40L expression on neutrophils from SLE patients and contribution of these OX40L + neutrophils in SLE pathogenesis to modulation of the B cell helper role of CD4 T cells. Methods: Surface expression of co-stimulatory molecules (OX40L, ICOSL, GITRL, 4-1BBL) on neutrophils from SLE patients and healthy donors (HD) was measured by flow cytometry (FC). Neutrophils from HD were stimulated with TLR7 or TLR8 agonists and IFNα after 5 hours of culture, OX40L expression was measured by FC and Western Blotting. CD4 T cells were cultured with the stimulated neutrophils for 3 days. At the end of the co-culture, percentages of IL21-expressing T follicular (Tfh) and peripheral helper (Tph) cells measured by FC. These generated T cells were also cultured in the presence of memory B cells. After 5 days of co-culture, plasmablast generation and Ig levels were assessed by FC and ELISA, respectively. Inhibition of OX40-OX40L interaction in vitro was achieved using ISB 830, a novel anti-OX40 mAb currently used in clinical trials. Results: Among the co-stimulatory molecules tested, percentages of OX40L + neutrophils in SLE (n=54) were increased compared to HD (n=25)(mean + SD: HD = 1, 34%±1.62 vs SLE = 4, 53%±8.1; p=0.29). OX40L expression positively correlated with SLE disease activity score (SLEDAI) (p = 0, 04; r = 0, 31) and with anti-DNA antibodies (p= 0, 04, r = 0, 33). Of note, the percentage of OX40L + neutrophils was higher in anti-sm-RNP + patients (n=16, mean= 9%±9.8), compared to anti-sm-RNP - patients (n=27, mean = 1, 4%±2.5; p = 0, 02). The percentage of OX40L + neutrophils was higher in patients with class III or IV lupus nephritis, and inflammatory infiltrate within the kidney biopsy disclosed OX40L + neutrophils, in close contact with T cells. Neutrophils from HD express OX40L with TLR8 agonist, or IFNα priming followed by TLR7 agonist. When memory CD4 T cells were cultured in the presence of TLR8-stimulated neutrophils, the proportion of IL21-expressing Tfh (CXCR5 + PD1 + ) and Tph (CXCR5 - PD1 hi ) were increased, compared to culture with unstimulated neutrophils. This process was dependent on OX40-OX40L interactions, since in vitro treatment with the anti-OX40 blocking antibody ISB 830, inhibited the differentiation of memory T cells into Tfh and Tph. Both generated Tfh and Tph were able to promote the differentiation of memory B cells into Ig-secreting plasmablasts. Conclusion: Our results disclose an unprecedented phenomenon where cross-talk between TLR7/8-activated neutrophils and CD4 lymphocytes operates through OX40L-OX40 costimulation, and neutrophils promote the differentiation of pro-inflammatory Tfh and Tph, as well as IL21 production. Therefore, OX40L/OX40 should be considered as a potentially therapeutic axis in SLE patients. References: [1]Jacquemin et al. Immunity 2015; [2]Jacquemin et al. JCI Insight 2018 Disclosure of Interests: Angela Pappalardo Grant/research support from: Ichnos Sciences, Elodie Wojciechowski: None declared, Itsaso Odriozola: None declared, Isabelle Douchet: None declared, Nathalie Merillon: None declared, Andrea Boizard-Moracchini: None declared, Pierre Duffau: None declared, Estibaliz Lazaro: None declared, Marie-Agnes Doucey Employee of: Ichnos Sciences, Lamine Mbow Employee of: Ichnos Sciences, Christophe Richez Consultant of: Abbvie, Amgen, Mylan, Pfizer, Sandoz and UCB., Patrick Blanco Grant/research support from: Ichnos Sciences